Necrosis, haemorrhage and complement depletion following bites by the spitting cobra (Naja nigricollis). - Warrell, D; Greenwood, B; Davidson, N; Ormerod, L; Prentice, C (1976)
The Spitting Cobra, Naja nigricollis, is widely and densely distributed in Africa. Fourteen patients with proven N. nigricollis bites, who were seen in the savanna region of Nigeria, did not exhibit the neurological signs, such as cranial nerve lesions and respiratory paralysis, expected following Elapid poisoning. All had local swelling, in eight cases involving the entire limb, and ten developed local tissue necrosis. Spontaneous haemorrhage was detected in three cases and was the probable cause of death in one of them; the other death in this series was unexplained. Haematological abnormalities included prolonged clot lysis anf failure of clot retraction due to a platelet defect. There was no specific deficit in clotting factors and a delayed rise in fibrin degradation products was attributed to extensive tissue damage at the site of the bit. Most patients showed depletion of complement component C3 and glycine-rich beta-glycoprotein (GBG), suggesting activation of the alternative pathway of complement fixation. There was evidence of hepatocellular damage in two out of six patients investigated. There was no evidence that specific polyvalent antivenoms, used in doses of up to 80 ml, prevented any of the effects of N. nigricollis venom. Clinical laboratory diagnosis is discussed. In the past many bites were wrongly classified as viper bites on the basis of clinical findings. Immunodiagnosis is a promising method for assessing the true importance of N. nigricollis bite in West Africa.